Evaluasi Penerapan SITB pada Klinik Swasta di Kota Denpasar dengan Metode HOT-FIT - Putra, Gede Wirabuana; Pradnyani, Putu Erma (Politeknik Negeri Jember, 2025)
Tuberculosis (TB) incidence in Indonesia ranks second highest globally, with case detection supported by the Tuberculosis Information System (SITB). In Bali Province, the majority of TB cases are concentrated in Denpasar City. This study aimed to evaluate the implementation of SITB in private clinics in Denpasar using a qualitative design with the Human, Organization, Technology, and Net Benefit (HOT-FIT) evaluation framework. Data were collected through in-depth interviews with six purposively selected informants from private clinics applying the Public–Private Mix (PPM) strategy and analyzed using thematic content analysis. The findings showed that, in terms of the Human factor, SITB was easy to use with relatively good user satisfaction, although staff competencies were not fully aligned; in terms of the Organization factor, medical record professionals were not yet involved in SITB reporting; in terms of the Technology factor, SITB quality was considered good, with user-friendly web-based access and available guidelines; and in terms of the Net Benefit factor, SITB improved efficiency in TB recording and reporting, although financial benefits remained limited. The study recommends strengthening human resource capacity in health information management, simplifying SITB data, and reinforcing government–private sector collaboration to support Indonesia’s TB elimination target by 2030.